2020
DOI: 10.5507/euj.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Youth Players During Wheelchair Basketball Games

Abstract: The purpose of this study was to document physiological responses that result from participation in youth wheelchair basketball (WCB) games. Each participant (4 males, 2 females, mean age = 15.2 y, SD= 1.8 y) completed a peak aerobic capacity upper-body cycle ergometer test until fatigue. Additionally, each participant competed in two regular season youth WCB games while wearing a Polar Pro Team System heart rate (HR) monitor. During competition, average HR, peak heart rate (HRpeak), playing intensity, total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
1
0
1
Order By: Relevance
“…The differences are small; however, these results are similar to those found by Pérez et al [44] in which the range of HR was between 131 and 152 beats per minute. Similarity, Conners et al [45] reported that the average HR was around 140 beats per minute. Regarding the % maximum HR, this value was around 69%, so it is demonstrated that the game is very demanding considering the cardiovascular requirements [46].…”
Section: Discussionsupporting
confidence: 74%
“…The differences are small; however, these results are similar to those found by Pérez et al [44] in which the range of HR was between 131 and 152 beats per minute. Similarity, Conners et al [45] reported that the average HR was around 140 beats per minute. Regarding the % maximum HR, this value was around 69%, so it is demonstrated that the game is very demanding considering the cardiovascular requirements [46].…”
Section: Discussionsupporting
confidence: 74%
“…Currently, wheelchair basketball is one of the adapted sports studied by researchers from different fields such as: physiology (Antonelli et al, 2020;Barboza et al, 2019;Conners et al, 2020;Feter et al, 2018;Galea et al, 2018;Marzsalek et al, 2019;Peters et al, 2020), biomechanics (de Witte et al, 2016;Marjolaine et al, 2018;Sasadai et al, 2020;Zacharakis, 2020), medicine (Hollander et al 2020), motor skills (Maksym et al 2018;de Witte et al, 2018), psychology (Qasim et al, 2019;Yeats et al, 2019), or sociology (Molik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Teniendo en cuenta esto, y con el fin de mejorar el rendimiento de los jugadores, a los largo de los últimos años se ha ido incorporando en el diseño de tareas de entrenamiento las conocidas como «Small Side Games», que se muestran eficientes para entrenar las capacidades físicas de los deportistas de BSR de forma integrada (Delextrat & Martinez, 2014;Yanci et al, 2014), mostrando diferentes respuestas fisiológicas en aquellos jugadores con lesión medular, en comparación con los deportistas que presentan una de lesión no medular (amputación, parálisis cerebral o poliomielitis) (Iturricastillo et al, 2016a;Iturricastillo et al, 2016b). Además, el BSR ha sido estudiado desde otras áreas de conocimiento como la fisiología (Antonelli et al, 2020;Barboza et al, 2019;Conners et al, 2020;Peters, Rice & Bull, 2020), biomecánica (De Witte et al, 2016;Marjolaine et al, 2018;Sasadai et al, 2020;Zacharakis, 2020), o psicología (Kokaridas et al, 2009;Skordilis & Stvrou, 2005).…”
unclassified